Forest fires as potential triggers for production and mobilization of polycyclic aromatic hydrocarbons to the terrestrial ecosystem. (29th August 2019) - Campos, Isabel; Abrantes, Nelson; Pereira, Patrícia; Micaelo, Ana Cristina; Vale, Carlos; Keizer, Jan Jacob
Abstract : Although forest fires have been identified as an important source of polycyclic aromatic hydrocarbons (PAHs), this problematic has not been thoroughly studied yet. This study addressed the role of wildfires and time since fire in the production and mobilization of PAHs to the terrestrial compartment. Levels of 15 priority PAHs were assessed in topsoil and ash samples (by GC–MS analysis) collected in two burnt areas and an unburnt one, comprising two types of vegetation coverage and four sampling occasions after fire. The fire had triggered an immediately increase of PAH levels in topsoil, according to the comparison of burnt and unburnt samples, but this impact had largely faded 4 months later. Although the fire severity did not play a role in immediate postfire PAH contents in topsoil and ashes, variations were found with the type of vegetation coverage being higher in pine slopes. The wildfire event markedly changed PAHs composition through enrichment in three‐ring PAHs (69% vs. 27%, burnt and unburnt, respectively), which dwindled more markedly in topsoil than in ashes. This study pointed out the key role of wildfires as a source of PAHs to the terrestrial compartment, as unveiled by the increased levels in topsoil and ashes. Additionally, it was found that PAHs could be mobilized from these matrixes over the first year after the fire, possibly leading to aquatic contamination. This finding suggests wildfires as a diffuse source of PAH contamination to freshwater systems, which need to be considering in future monitoring/management programs on the environmental impact of wildfires.